Indication of Heavy Metals and Coliform Bacteria in Tap Water of Al-Karkh Side Hospitals-Baghdad, Iraq - Hameda Khadem Zgair (World Journal of Experimental Biosciences, 2024)
The correlation between the quality of drinking water provided to healthcare facilities and the quality of healthcare services rendered to individuals is crucial. The objective of this present investigation is to assess the presence of heavy metals and coliform bacteria (indicating contamination with pathogenic bacteria from fecal matter) in the tap water distributed to the Al Karkh area of Baghdad. Specifically, tap water samples were collected from four hospitals situated in the Al Karkh region of Baghdad, namely Al Karama Teaching Hospital, Albishara private hospital, Al-karkh private hospital, and Karkh Hospital For Childbirth. The levels of heavy metals, including copper (Cu), zinc (Zn), lead (Pb), and cadmium (Cd), were evaluated, as well as the presence of coliform bacteria (a marker for pathogenic contamination). The findings revealed that the levels of heavy metals complied with the standard values in all hospitals under study, except Cd, which exceeded the standard level in the tap water collected from Albishara private hospital and Karkh Hospital for Childbirth. Moreover, no coliform bacteria were detected in any of the tap water samples obtained from the hospitals investigated. As such, it can be inferred that the quality of water, in terms of heavy metal levels, supplied to these four hospitals adhered to the standard regulations, and all samples were free from coliform bacteria, which indicates the absence of fecal contamination in the water provided to these healthcare facilities.
Keywords: Al Karkh/side, Coliform, Drinking water, Heavy metals, Hospitals, Pathogenic bacteria.